Inmate radicalisation and recruitment in prisons - Jones, Clarke (Routledge advances in sociology, 2019)
Cover; Half Title; Series Page; Title Page; Copyright Page; Dedication; Table of Contents; List of illustrations; Acknowledgements; List of abbreviations; Chapter 1; Introduction; Note; Bibliography; Chapter 2; The inmate social system and coping with the pains of imprisonment; Early Western perspectives on inmate social systems; Inmate code and solidarity; Inmate leadership structure; Deprivation perspective; Importation perspective; Managerial perspective; Bibliography; Chapter 3; Religion and rehabilitation in prisons; Prison conversions; Role of religion; De-radicalisation; Bibliography